2018
DOI: 10.3171/2017.5.spine161154
|View full text |Cite
|
Sign up to set email alerts
|

Cortical bone trajectory screw fixation versus traditional pedicle screw fixation for 2-level posterior lumbar interbody fusion: comparison of surgical outcomes for 2-level degenerative lumbar spondylolisthesis

Abstract: OBJECTIVEThe cortical bone trajectory (CBT) screw technique is a new nontraditional pedicle screw (PS) insertion method. However, the biomechanical behavior of multilevel CBT screw/rod fixation remains unclear, and surgical outcomes in patients after 2-level posterior lumbar interbody fusion (PLIF) using CBT screw fixation have not been reported. Thus, the purposes of this study were to examine the clinical and radiological outcomes after 2-level PLIF using CBT screw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 16 publications
6
66
0
2
Order By: Relevance
“…The results were consistent with that in similar cohorts [31]. The average surgical time ranged from 117.8min to 237.6min [8,20], and 119ml to 276.5ml [21,32] for intraoperative blood loss in previous studies of single level cortical screw fixation surgery [21,[32][33][34].…”
Section: More Familiar With Surgical Procedures: a Natural Processsupporting
confidence: 85%
See 1 more Smart Citation
“…The results were consistent with that in similar cohorts [31]. The average surgical time ranged from 117.8min to 237.6min [8,20], and 119ml to 276.5ml [21,32] for intraoperative blood loss in previous studies of single level cortical screw fixation surgery [21,[32][33][34].…”
Section: More Familiar With Surgical Procedures: a Natural Processsupporting
confidence: 85%
“…The superior pullout strength, higher insertional torque and satisfactory stability of the screw-rod construction compared to the traditional fixation have been confirmed by biomechanical studies [7,10,[12][13][14][15][16][17][18]. And the comparable clinical outcomes, less multifidus muscle damage and less complications associated with instrumentations compared to PS have been observed in clinical studies [19][20][21][22][23][24]. However, the CBT screws placement accuracy, surgical parameters and complications in one surgeon's learning curve could rarely be found in literature.…”
Section: Introductionmentioning
confidence: 78%
“…Although this difference has been seen in some studies, 11,13,16 others have reported similar EBL. 17 As with operative time, differences in surgeon familiarity with the technique and body mass index among patient cohorts can potentially obscure the perceived benefits of the less invasive exposure associated with CBT screws. Increased blood loss during lumbar fixation has been correlated with increased muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the largest CBT screw cohort to date did not report on the incidence of screw pullout or loosening. 17 Larger comparison studies are needed to determine whether or not the biomechanical advantages of CBT screws can be replicated in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…The screw is placed at an inward and outward tilt to maximize the contact with cortical bone. It has the advantages of strong control, less trauma, fewer complications, less intraoperative bleeding and lower postoperative infection rate [14][15][16], which has a broad clinical value and application prospect. However, there are still risks and postoperative complications in clinical practice, including failure of internal fixation, pedicle splitting, pseudarthrosis and dural tear.…”
Section: Development Change and Limitation Of Spinal Fixation Technomentioning
confidence: 99%